2004
DOI: 10.4269/ajtmh.2004.70.38
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction Monitoring of Transmission of Onchocerca Volvulus in Two Endemic States in Mexico

Abstract: To investigate the impact of mass ivermectin treatments in Mexico on Onchocerca volvulus transmission, entomologic surveys were carried out in the two endemic states of Oaxaca and Chiapas. The data suggest that substantial progress towards the goal of elimination has been made. A comparison pre- and post-ivermectin data from a community in Southern Chiapas showed a 97% decrease in seasonal transmission potential, but some level of polymerase chain reaction positivity was still detectable. In other communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 31 publications
1
63
0
1
Order By: Relevance
“…6 The separated head and body pools were tested for O. volvulus parasites by using a PCR assay specific for O. volvulus . Details of protocols for genomic DNA purification, primer sequences, PCR conditions, and detection of PCR products by enzyme-linked immunosorbent assay (ELISA) have been published elsewhere.…”
Section: Study Areamentioning
confidence: 99%
“…6 The separated head and body pools were tested for O. volvulus parasites by using a PCR assay specific for O. volvulus . Details of protocols for genomic DNA purification, primer sequences, PCR conditions, and detection of PCR products by enzyme-linked immunosorbent assay (ELISA) have been published elsewhere.…”
Section: Study Areamentioning
confidence: 99%
“…Black flies were obtained and head pools of ≤ 100 heads were processed for O. volvulus -specific the O-150 polymerase chain reaction (PCR) and PCR-based enzyme-linked immunosorbent assay (ELISA) as reported. [15][16][17] A sample was considered putatively positive if it had an ELISA score at or above the cutoff (i.e., the mean of 10 internal negative controls plus 3 SD). Samples positive after a second independent PCR and ELISA were reported as confirmed positive.…”
mentioning
confidence: 99%
“…[2][3][4][5] However, entomologic and serologic studies carried out in 2001 and 2005 indicated that autochthonous transmission of O. volvulus might be occurring in the northern Chiapas focus, albeit at a low level. [6][7][8] The conclusion that transmission of O. volvulus is rare or non-existent in northern Chiapas is supported by the clinical incidence reports from the local health officials. The last five new clinical cases (i.e., individuals diagnosed positive for nodules or skin microfilariae [mf] for the first time) were reported in 1996 ( Figure 2 ), when four individuals who had traveled outside of northern Chiapas were found to contain mf in skin snips.…”
Section: Introductionmentioning
confidence: 88%
“…Entomologic study. Black flies were collected by using standard procedures 6,11 from February to May 2005 coinciding with the peak O. volvulus transmission season. 12 The collections were carried out during the first 50 minutes of Black flies were collected before they began feeding.…”
Section: Introductionmentioning
confidence: 99%